Using Biomedical Physics and Nano Technology to Combat Antibiotic Resistance: A Novel Approach - Ali, Muna Khalifa (American Journal of Biology and Natural Sciences, 2026)
The rising epidemic of antimicrobial resistance (AMR) is among the most significant threats to the global population health of the 21 st century. Since multidrug-resistant (MDR) microorganisms never cease developing biological processes to overcome the traditional methods of chemical treatment, the necessity to appear as an absolute paradigm shift in therapeutic procedures has become absolute. This theoretical research paper suggests a new interdisciplinary solution between biomedical physics and nanotechnology to fight MDR pathogens. To go beyond traditional biochemical inhibition, the paper will build a theoretical foundation to examine a biophysical mode of action Photothermal Therapy (PTT) involving the use of polyethylene glycol (PEG)-functionalized Gold Nanorods (AuNRs) as nanoscale transducers. This paper, through the perspectives of localized surface plasmon resonance (LSPR) and thermodynamic analysis, assesses the theoreticality of transformation of Near-Infrared (NIR) laser energy (808 nm) into intense and highly localized nanoscale hyperthermia. Theoretical models suggest that this high-speed thermal stress is adequate to physically interrupt bacterial cell wall envelopes - inducing disastrous lipid phase transitions in Gram-negative bacteria and protein structure denaturation in Gram-positive ones. Moreover, the conceptual model illustrates the thermodynamic degradation of the viscoelastic extracellular polymeric substance (EPS) of recalcitrant biofilms. More importantly, since this process depends on the inherent physical and thermodynamic constraints of biological macromolecules, instead of particular metabolic processes, the chances of bacteria becoming genetically resistant to such acute physical damage are theoretically removed. Also, the study defines a theoretical therapeutic window within which the property of differentiating heat dissipation helps to prevent the thermal damage of vascularized mammalian tissues. Finally, this theoretical study postulates that the use of physical forces and the specific thermal stress can provide a highly sustainable, resistant-immune solution of infectious diseases in the forthcoming post-antibiotic era.